A PFA methodology to investigate UD composites in fatigue comprising a KTF-based model for matrix damage and stochastic fiber failure prediction. (1st January 2022) - Bhuiyan, Faisal H.; Fertig, Ray S.
Highlights: Interaction of matrix cracking, delamination, and fiber failure modeled and validated. Fiber-aligned mesh and adaptive cycle jumping used for model efficiency. Studied role of each subcritical damage mode in PDA of multidirectional composites. Stochastic fiber failure predicts a range of composite failure modes in OHT coupons. Abstract: A physics-based, multiscale, progressive fatigue damage analysis methodology for continuous fiber-reinforced polymer composites was further developed and applied to the problem of fatigue damage prediction in open hole tension (OHT) coupons comprised of multidirectional laminates undergoing tension–tension loading. Based off lamina level calibration data, cumulative damage analysis of matrix and fiber constituents under cyclic loading condition was implemented with the objectives to: (i) predict the onset and the progression of subcritical matrix failures as well as the ultimate failure due to fiber fracture, and (ii) observe the effects of damage mode interactions on the progressive failure process. A kinetic theory of fracture (KTF) based durability prediction methodology was utilized to keep track of the matrix damage transpiring in the intra- and inter-laminar layers of the laminate. Tensile strengths were randomly assigned to the fibers using two-parameter Weibull statistics, while the maximum stress theory in tandem with the linear damage accumulation rule was applied to capture the tensile rupture of the reinforcements. Progressive fatigue damage prediction of OHT coupons consisting of the unidirectional composite IM7/977-3 and layup schedules of [0/45/90/−45]2S and [60/0/−60]3S were carried out and benchmarked against available experimental data. It was observed that the KTF-based fatigue model captured the damage state at individual layers, overall loss of mechanical performance, and stochastic nature of the ultimate failure well. The effects of interactions among the damage modes, namely matrix cracking, delamination, and fiber rupture were also investigated and it was recognized that such interactions are a critical feature of the progressive failure process in composite structures.